What is the wind behind this sail - can fund managers successfully time their investment styles? - Lu, Jeffrey Junhua (Cranfield University, 2005)
There is a considerable body of literature that examines the behaviour of institutional investors as a potential source of market price movement. Most existing studies focus on the market timing abilities of active fund managers and find mixed evidence for their fund timing skills. However, few studies have investigated fund manager timing abilities within segments of the market, such as factor timing and sector timing. This study investigates the style timing behaviour of US domestic equity funds existing at any time during the period 1_2-2002. Specifically, I examine the timing activities of actively managed mutual funds within different market segments based on such established systematic risk factors as size, book-to-market, momentum, and across different fund styles such as aggressive growth, growth and income, and small company funds, etc. Mutual fund timing strategy can be viewed as the fund manager's response to hislher private information regarding future factor premiums. Instead of directly observing how fund managers make their timing decisions, an alternative approach is to look at the direct outcomes of their decisions, which are related to the factor timing loadings derived from a factor timing model. I significantly expand on the work of Bollen and Busse (2001) and Volkman (l~ by combining systematic risk factors unique to equity markets with timing factors unique to actively managed portfolios. Within this empirical timing-activity evaluation framework, I additionally investigate fund timing behaviour in the context of Morningstar star rating performance record, investment objectives, fund age, turnover, and load expense, etc. This Ph.D. is an original contribution to the literature of fund timing activities, which seeks to contribute to our understanding in terms of investigating mutual fund managers' timing strategies with respect to specific systematic risk factors and their evolution over time. This research has important implications both for extant asset pricing theories and for practitioners especially in the evaluation of portfolio performance and investigation of fund managers' timing activities.